2018
DOI: 10.15835/nbha46211183
|View full text |Cite
|
Sign up to set email alerts
|

Flower Development in Walnut: Altering the Flowering Pattern by Gibberellic Acid Application

Abstract: The pattern of walnut flowering varies depending on genetic and environmental factors. To study the patterns of walnut pistillate flowers developing as a result of applying gibberellic acid (GA 3 ), the research was conducted as a factorial design with 2 factors (three levels of trunk diameter (10 to 12 cm, 12 to 14 cm and 14 to 16 cm) and four levels of GA 3 (0, 50,100 and 200 mg/l)) on 'Chandler' commercial cultivar. Different levels of GA 3 were sprayed twice on the trees, i.e. 2 and 4 weeks after flowering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…'Xinxin2' are relatively rich in natural conditions, which provides an opportunity to test the hypothesis proposed in this paper. According to literature, there were many studies on walnuts, such as walnut flowering (Hassankhah et al 2018), bud dormancy (Gholizadeh et al 2017), ex vitro acclimation of walnut plantlets (Maleki Asayesh et al 2017a,b), etc. Previous studies showed that photosynthesis of walnut leaves was affected by many factors, including kaolin (Rosati et al 2007, Gharaghani et al 2018, rootstock varieties (Li et al 2017), fertilizers (Nicodemus et al 2008, Liu et al 2010), acclimation (Chenevard et al 1997, light (Dean et al 1982, Atanasova et al 2003, salinity (Zhang et al 2002), and water (Scartazza et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…'Xinxin2' are relatively rich in natural conditions, which provides an opportunity to test the hypothesis proposed in this paper. According to literature, there were many studies on walnuts, such as walnut flowering (Hassankhah et al 2018), bud dormancy (Gholizadeh et al 2017), ex vitro acclimation of walnut plantlets (Maleki Asayesh et al 2017a,b), etc. Previous studies showed that photosynthesis of walnut leaves was affected by many factors, including kaolin (Rosati et al 2007, Gharaghani et al 2018, rootstock varieties (Li et al 2017), fertilizers (Nicodemus et al 2008, Liu et al 2010), acclimation (Chenevard et al 1997, light (Dean et al 1982, Atanasova et al 2003, salinity (Zhang et al 2002), and water (Scartazza et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The wood and fruit of walnut ( J. regia L.) are highly valuable, and the research of walnut focus on molecular breeding and flowering in recent years [ 60 – 65 ]. However, less attention were paid to walnut compare with other plants, because it must grow for many years before it becomes productive.…”
Section: Introductionmentioning
confidence: 99%
“…The buds were sampled throughout the year with 14-day intervals and were fixed overnight in fixation solution (including 10% formaldehyde + 5% acetic acid + 50% ethanol). The buds were cut vertically with a sharp razor and were stained with methylene blue and carmine [61]. The microscopy technique (Nikon Eclipse E200, Japan) was used for the determination of flower development stage.…”
Section: Determining the Time Of Flower Induction Initiation And Difmentioning
confidence: 99%